ANALISIS KESESUAIAN PENERAPAN SAFETY SIGN DI PT. TERMINAL PETIKEMAS SURABAYA - Febry Eka Saputra (The Indonesian Journal of Occupational Safety and Health, 2016)
Safety sign is the equipment contained in the work environment in order to protect and enhance the awereness of workers against potential dangers which are occur in the work environment. This research was conducted to find out the suitability of applying the safety sign on work environment based on ANSI Z535 standard. This Research is observational with cross sectional design. Data collection was done by direct observation using ANSI Z535 safety sign checklist within a certain time. There are 5 types of safety sign based on the ANSI Z535standard researched. They are danger sign, warning sign, sign, sign the notice caution and safety condition sign. Field observation was retrieved results suitability against ANSI Z535 standard with highest suitability figures on danger sign fulfill 8 of 16 items (50%), warning sign fulfill 6 out of 16 items (37.5%), caution sign fulfill 9 out of 16 items (56.25%), notice the sign fulfill 9 dari14 items (68.28%), and safety condition sign fulfill the entire item (100%). Conclusions on the research was application of a danger sign, warning sign, sign, and caution notice sign have not been suit with ANSI standard Z535. While the safety condition sign has been suit. HSSE management should have been did a monitoring, evaluation and improvement against the safety sign that damaged and did not suitable with the standards in International and Domestic Docks PT. Terminal Petikemas Surabaya.Keywords: suitability, safety sign, ANSI Z535